Servicescape and Customer Satisfaction at The Bulog Makassar Branch Office - Inka Inka; Muh Rizal S; Muh Nur Yamin (Universitas Negeri Makassar, 2026)
Servicescape and Customer Satisfaction at Perum Bulog Makassar Branch Office. Thesis. Business Administration Study Program. Faculty of Social Sciences and Law. Makassar public university. Supervised by Nur Yamin and Maya Kasmita.This study aims to determine how the influence of Servicescape and Customer Satisfaction at Perum Bulog Makassar Branch Office. To achieve this goal, researchers use indicators to measure these variables. In the Servicescape variable, the indicators used are environmental cleanliness, facility temperature, proper lighting, attractive architecture, interior, physical facilities, a good place to rest, work together, and be friendly. As for the Customer Satisfaction variable, the indicators used are suitability of expectations, interest in revisiting, Willingness to recommend. In this study the research methods used were observation, questionnaires, and documentation. The sample used in this study was 80 respondents. The data were obtained from the results of the research which were processed using data analysis and using the help of the SPSS version 25 software program which consisted of validity tests, reliability tests, normality tests, simple linear regression analysis, and the coefficient of determination.The results of the study show that the indicators used for each of these variables indicate that the Servicescape variable has a significant influence on customer satisfaction at the Perum Bulog Makassar Branch Office. This is evidenced by the test of the coefficient of determination using the data that has been obtained.